How Educators of Teachers of Science Evaluate Biology Teachers - Dieter, Donn.; North Carolina State Dept. of Public Instruction, Raleigh. Div. of Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This study attempted the following: a) to establish the criteria that judges used in the Outstanding Biology Teacher Award Program to evaluate biology teachers, b) to identify their various occupations, c) to establish whether or not criteria were valued significantly differently, and d) to determine if occupational status of judges is significantly related to such ratings. Regarding evaluation of biology teachers, it is possible to say that touchstones do exist which are significant for competent judges. Also, concerns for evaluator bias are real worries, for various judges do value specific criteria differently, and professors of science education and college biologists differ somewhat in how they value specific criteria. (Results of the evaluation of data are included in the text.) (Author/JA)
ERIC Note: Paper presented at the AETS Mid-Atlantic Regional Meeting of the National Science Teachers Association, Norfolk, Virginia, November 1973.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Biology; Evaluation Methods; Science Instruction; Science Teachers; Teacher Educators; Teacher Effectiveness; Teacher Evaluation